2007
DOI: 10.1119/1.2372470
|View full text |Cite|
|
Sign up to set email alerts
|

Ion acoustic wave experiments in a high school plasma physics laboratory

Abstract: We describe a successful alliance between a university and several high schools. The alliance is centered on a laboratory experiment constructed by students and faculty. The experiment involves sophisticated concepts and equipment not readily available in high schools. Much of the experiment is directly related to the science and mathematics learned in high school, with opportunities to extend their understanding by applying it to a research experience. The experiment is in plasma physics, but a similar allian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Fascinating phenomena may emerge from the interplay between electromagnetism, fluid dynamics and quantum physics in plasma physics. Several experimental devices have recently been designed as educational tools at the undergraduate level [1][2][3][4][5][6][7]. Widely used, fluorescent tubes or other plasma-based lighting devices remain an affordable and simple way to introduce several fundamental concepts of plasma physics [8][9][10][11][12].…”
Section: Physical Phenomenon and Article Outlinementioning
confidence: 99%
“…Fascinating phenomena may emerge from the interplay between electromagnetism, fluid dynamics and quantum physics in plasma physics. Several experimental devices have recently been designed as educational tools at the undergraduate level [1][2][3][4][5][6][7]. Widely used, fluorescent tubes or other plasma-based lighting devices remain an affordable and simple way to introduce several fundamental concepts of plasma physics [8][9][10][11][12].…”
Section: Physical Phenomenon and Article Outlinementioning
confidence: 99%
“…The Ion-Acoustic Waves (IAWs) are the primary example of low frequency electrostatic compressional modes in gaseous plasmas. The contribution of the ions in the IAWs is same as of the neutral atoms/molecules in sound waves 13 propagating in neutral fluids. The interaction of ions in the plasmas extends over the long distances by their electric fields and therefore the IAWs do propagate even in collisionless gaseous plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…The LAPTAG students and teachers played a large role in the fabrication of the device, with the help of their faculty advisors, and the research resulted in a publication. 1 In 2007 a magnetized plasma device was constructed in the LAPTAG lab to replace the original machine, and is there for the sole use of high school students. The addition of a magnetic field opened up the possibility for the study of a large variety of waves including drift waves, which were observed on the plasma edge.…”
Section: Introductionmentioning
confidence: 99%